Peran self-compassion dan spiritualitas terhadap depresi pada ibu hamil - Chairunnisa, Alfira; Fourianalistyawati, Endang (Konsorsium Psikologi Ilmiah Nusantara, 2019)
Pregnancy is a significant event that causes changes both physically and psychologically among pregnant women. Hence, it can trigger symptomps of depression during pregnancy. Previous studies have shown that self-compassion significantly correlated with depression, as well as spirituality. Therefore, the purpose of this study was to examine the role of self-compassion and spirituality toward depression among pregnant women simultaneously. The sample of this study was pregnant women who had completed Edinburgh Postnatal Depression Scale (EPDS), Self-Compassion Scale (SCS), and Daily Spiritual Experience Scale (DSES) (n = 125). The result of multiple regression analysis showed that self-compassion and spirituality have significant roles in predicting depression among pregnant women simultaneously. A higher score of self-compassion could predict a lower score of depression, even when the score of spirituality was being controlled. The self-judgement and perception of transcendent events dimensions have significant contributions toward depression among pregnant women.